Vitamin A Program for Giving Toddlers in Posyandu Neighborhoods Ledeng with CIPP Model - Aq Zahra, Dera Isgi; Wahyudin, Uyu; Sukmana, Cucu (Universitas Pendidikan Indonesia (UPI), 2023)
This study aims to evaluate the facilities of the Posyandu (Integrated Health Service Post) in the vitamin A supplementation program for toddlers at Posyandu Ledeng. The vitamin A supplementation program at Posyandu Ledeng was evaluated using the CIPP (Context, Input, Process, Product) model to assess the program's context, resources utilized, program implementation, and achieved outcomes. The evaluation results showed that although the vitamin A supplementation program was implemented successfully, there are still deficiencies in the available facilities. The measuring equipment for body weight and height and the storage facilities for vitamin A are inadequate, and there is a need to replenish the vitamin A stock. These facility shortcomings can impact the program's effectiveness and the quality of healthcare services at Posyandu Ledeng. Therefore, it is necessary to update and improve the facilities and inventory management to enhance the effectiveness of this program, ensuring its sustainability and success in providing vitamin A supplementation to toddlers at Posyandu Ledeng.